Editorial - Preudhikulpradab,Ph.D., Sirichai (ABAC ODI JOURNAL Vision. Action. Outcome, 2015)
This issue of the ABAC ODI Journal. Vision.Action.Outcome comprises of five articles which stem from researches and OD implementations. The contributing authors are Dr.Jay Finkelman, Dr.Salvacion Villavicencio, Dr.Lee Hsing, Diah Dharmayanti, and Panarai Polyapipat. The first three authors are currently the university professors and organization practitioners in the field of Organization Development, teaching both Doctoral and Master levels while the remaining two authors are the graduating students at Doctorate and Master Levels in Organization Development, Tourism and Hospitality. Each of these articles provides rich perspectives, processes, principles and practices from lenses of OD academia, educator, OD practitioners and business practitioners. The first article is by Dr.Jay Finkelman. The author employs Meta-Analytic approach to conceptually interpret the constructs of Emotional intelligences (EI) and articulates how EI can positively influence the understanding and behavior of the person toward the ability to lead and pursue the organization development and organization effectiveness. The second article, titled “Whole Brain Literary Approach to Action Research” by Dr.Salvacion Villavicencio presents the process of teaching action research for her graduate students in Master of Management and Organization Development, utilizing the Whole Brain Literacy (WBL) as a model and a tool in enabling students to define critical issues prior to and during the implementation of an Action research to cause positive change and transformation. The third article, titled “Soaring towards Positive Change” by Dr. Lee Hsing Lu is an Action Research case study in Double Loop Learning Process, involving both Thailand and Indonesia as study groups. The emphasis is placed on the employment of S.O.A.R as an OD change process and tool to enable and manage strategic planning and problem solving situations while embracing Hofstede’s cultural dimensions values to describe, discern and identify how S.O.A.R can appropriately be utilized for Organization strategic development. The four article titled “Improving Internal Marketing Program as Organization Development Intervention to Enhance Market Performance” by Diah Darmayanti and Dr. Susan Nero is an Action Research case study, together with planned OD interventions for change. The article presents the process of a change program and the outcomes of planned OD interventions demonstrate a shift from varied market orientation mindset and organizational commitment to a market-orientation mindset and commitment among organization leaders. The fifth article, titled “Tourists’ Understanding of The Elephant Business in the Tourism Industry” by Pannarai Polyapipa and Dr. Aaron Loh is an International Tourism case study in Chiang Mai province. The article presents a survey results of tourists’ understanding in assisting business owners to operate more ethically. The survey was conducted with 382 international tourists who visited elephant-base attractions. The results show that the majority of tourists understand ethical implication of elephant-based attraction and the trend of using animals in tourism for entertainment has recently become more ethical in its practice recently. In summary, this is another level of accomplishment and significance that ABAC ODI Journal Vision. Action. Outcome. with its contributing authors have made to the OD community. The articles represent various industries (e.g., business, education and tourism), together with diverse of organizational variables, ranging from emotional intelligences constructs to the organization effectiveness, the employment of Whole Brain Literacy (WBL) to enhance the quality of action research, the use of S.O.A.R as an OD change process and tool, incorporated with Hofstede’s cultural dimension concept, and the implementation of planned OD intervention to cause a shift of mindset among organization leader to market-orientation to the survey findings of tourist’s on their awareness of increased ethical practices in elephant-based attractions. We hope that interested readers would find the current issue of ODI journal as informative and educational while providing you with some practical ideas how you might employ them with your organizations, employees, students and community.